Formation of urban space on the territory of Vagharshapat - Gnuni , Artak; Mkrtchyan , Levon; Tadevosyan , Anzhela (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
Being located in the central part of the Ararat Valley, the territory of the city of Vagharshapat has been one of the most important centers of Armenia for thousands of years. The Early Bronze Age is marked by the emergence of the first large settlement agglomeration. The center of this agglomeration was probably the settlement of Mokhrablur. In the Late Bronze and Early Iron Ages the area of Vagharshapat, probably, was part of the Metsamorian agglomeration. In the Urartian period, the eastern part of the city, the area of Zvartnots (figuring as ‘Valley of Quarlini/Qublini’ in Urartian sources) was most likely included in the agricultural zone of the Urartian city of Teishebaini (Karmir-Blur). In the post-Urartian period, the citadel of Vardgesavan was located on the territory of Shresh Blur. Our materials on Vagarshapat, called Kaenopolis in the second half of the 2nd century BC, are fairly limited. Probably, it was a classic garrison town. The headquarters of the Legion was most likely located on the territory of the Main Cathedral. The topography of Vagharshapat was a continuation of Roman traditions. In its structure, the city was also similar to other contemporary cities. With the adoption of Christianity Vagharshapat became the seat of Catholicos, and the urban quarters were transformed into patriarchal residence.